ANALISIS DETERMINASI USAHA PERIKANAN TANGKAP NELAYAN DI KABUPATEN TOJO UNA-UNA - Dafina Howara; Alimuddin Laapo (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The research was aimed to determine the priority development of catch fishery enterprise in Tojo Una-Una Regency based on the feasibility aspects of biology, techniques, economy and social.  The present study used secondary and primary data, which then analyzed using descriptive and Fisheries Effort Determination Method.  Results showed that Longline fisheries were predominant among the existing catch fisheries enterprises in Tojo Una-Una Regency.  The determination analysis resulted in that the first priority in fisheries development in Tojo Una-Una Regency should be for Longline fisheries followed by Purse seine Fisheries, Gillnet fisheries, and Bagan fisheries